THE ROLE OF PSYCHOLOGICAL SUPPORT IN THE EDUCATIONAL ENVIRONMENT IN THE FORMATION OF PROFESSIONAL IDENTITY (Universal International Scientific Journal, 2026)
The article scientifically analyzes the impact of the educational environment, pedagogical communication, psychological support services, and mentoring on the learning process of professional identification in future vocational teachers, and highlights the quality of motivation, understanding, reflection, self-management, and personal-professional content as technical mechanisms of professional identification.
Keywords: Psychological mechanisms, professional identification, educational environment, medical support, psychological support, reflection, motivation, professional self-concept.